Planting Bamboo Palm to Reduce Air Pollution in Order to Maintain Lung Health in Pp. Assalafi Al Fithrah Surabaya - Irawan, Danny; Awwalia, Evi Sylvia; Yunita Sari, Ratna; Muhammad, Akbar Reza; Aditya Iryawan, Rifky Dwi; Nuari, Nuzlan; Oktaviana, Betta Mega; Avicenna, Adrian; Alifiyah Pramesti, Rosandhy (UNUSA Press, 2024)
Air quality in Surabaya is seriously challenged by motor vehicle emissions, industrial pollution, and lack of green space, which have a direct impact on public health, especially on the respiratory system, which can cause diseases such as asthma and bronchitis. To overcome this, a community service program using lecture and simulation methods was carried out, involving 40 male and female students at the Islamic boarding school. The lecture lasted 40 minutes with PPT and poster media, as well as pre- and post-test questionnaires to measure the increase in participants' knowledge. In addition, the simulation was carried out in collaboration with the Islamic boarding school in planting bamboo palms on May 11, 2024. The results showed a significant increase in students' knowledge regarding the benefits of bamboo palms as an effort to prevent air pollution, with a significant difference in pre- and post-test scores (p <0.05). The lecture approach accompanied by visual media has proven effective in increasing understanding of the role of bamboo palms in reducing pollution in the Islamic boarding school environment, so that this education has succeeded in increasing students' awareness of the importance of efforts to overcome air pollution.